Ethnicity and Recruitment of Personnel in the Delta State Civil Service - Nathaniel Oromoni; V. E. Efebeh; F. A. Ikenga (Journal of Social Science and Humanities, 2025)
This study investigates the influence of ethnicity on recruitment practices in the Delta State Civil Service, examining how ethnic considerations affect merit-based selection, workforce efficiency, and overall organizational performance. The study employed a cross-sectional research design and was guided by Weber’s Bureaucratic Theory, which emphasizes meritocracy, formal rules, and competence as the foundation of an effective public service. The study assesses the extent to which recruitment processes in Delta State conform to or deviate from these principles. The study population comprised 3,723 civil servants, from which a sample of 397 respondents was selected using a stratified sampling technique to ensure adequate representation across ministries and cadres. Out of the 397 questionnaires distributed, 341 were returned and analyzed. Three hypotheses guided the analysis. Findings from the first hypothesis confirm that ethnicity significantly influences recruitment decisions, often overriding merit and weakening transparency, contrary to Weberian expectations of impartiality and professionalism. The second hypothesis established a strong relationship between ethnicity-based recruitment and worker inefficiency, revealing that individuals appointed through ethnic patronage often lack the required competence, resulting in lower productivity and poor service delivery. This supports Weber’s argument that recruitment based on merit is vital for bureaucratic efficiency. The third hypothesis identified a moderate yet significant relationship between ethnicity and merit, showing that although meritocratic structures exist, ethnic pressures continue to undermine their implementation. The study concludes that ethnicity-based recruitment weakens institutional capacity, reduces efficiency, and hampers long-term development. It recommends, among others, that the Delta State government should strengthen transparent merit-based recruitment systems, enforce anti-discriminatory policies, and promote continuous professional development in line with Weberian principles to build a more accountable and performance-driven civil service in Delta State.